2018
DOI: 10.1101/444364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programmed DNA elimination of germline development genes in songbirds

Abstract: 24Genomes can vary within individual organisms. Programmed DNA elimination leads to dramatic 25 changes in genome organisation during the germline-soma differentiation of ciliates 1 , lampreys 2 , 26 nematodes 3,4 , and various other eukaryotes 5 . A particularly remarkable example of tissue-specific 27 genome differentiation is the germline-restricted chromosome (GRC) in the zebra finch which is 28 consistently absent from somatic cells 6 . Although the zebra finch is an important animal model 29 system 7 , m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, to the contrary, the sequence data presented here have revealed that there are many genes on the B. coprophila GRCs and they are paralogs of genes on the other chromosomes. Recently it has also been reported for other plants and animals that genes on eliminated DNA have paralogs in the other chromosomes [10,45]. Although it remains to be seen whether the multitude of B. coprophila GRC genes are transcribed and play an important role, with GRC genes now identified, future studies can elucidate when and where their transcription occurs and determine whether these chromosomes are necessary in B. coprophila.…”
Section: Function Of Grcs In Sciaridaementioning
confidence: 97%
See 2 more Smart Citations
“…However, to the contrary, the sequence data presented here have revealed that there are many genes on the B. coprophila GRCs and they are paralogs of genes on the other chromosomes. Recently it has also been reported for other plants and animals that genes on eliminated DNA have paralogs in the other chromosomes [10,45]. Although it remains to be seen whether the multitude of B. coprophila GRC genes are transcribed and play an important role, with GRC genes now identified, future studies can elucidate when and where their transcription occurs and determine whether these chromosomes are necessary in B. coprophila.…”
Section: Function Of Grcs In Sciaridaementioning
confidence: 97%
“…Recent genomic work on lampreys and nematodes (with chromatin diminution) and songbirds (with chromosome elimination) have found that the germline restricted portions of the genome often carry protein coding genes involved in germ tissue maturation and function [8][9][10][11]. Therefore, a leading hypothesis is that germline restricted DNA may help resolve intralocus conflict between the germline and somatic cells [10,12]. However, although chromatin diminution and chromosome elimination have similar consequences, the initial evolution of these systems probably differs, as the mechanism of elimination is substantially different in these two systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline-restricted chromosomes are probably widespread in the highly dynamic evolutionary history of songbirds, which leads to significant differences between the genome of germline cells and the genome of somatic cells. This is a new mechanism for minimizing the genetic conflict between germ line cells and somatic cells [20,21].…”
Section: Female Heterogametic Systemmentioning
confidence: 99%
“…Protein coding sequences are discarded in all these cases, and genes eliminated from somatic lineage cells are typically predicted to have functions in the germline and embryogenesis (Smith et al 2012;Bryant et al 2016). The songbird Taeniopygia guttata has a germline-limited chromosome that is deleted from somatic lineage cells (Pigozzi and Solari 1998;Pigozzi and Solari 2005;Itoh et al 2009;Biederman et al 2018;Kinsella et al 2019;Torgasheva et al 2019).…”
Section: Introductionmentioning
confidence: 99%